2017
DOI: 10.1007/s00572-017-0785-9
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizas are present on Spitsbergen

Abstract: A previous study of 76 plant species on Spitsbergen in the High Arctic concluded that structures resembling arbuscular mycorrhizas were absent from roots. Here, we report a survey examining the roots of 13 grass and forb species collected from 12 sites on the island for arbuscular mycorrhizal (AM) colonisation. Of the 102 individuals collected, we recorded AM endophytes in the roots of 41 plants of 11 species (Alopecurus ovatus, Deschampsia alpina, Festuca rubra ssp. richardsonii, putative viviparous hybrids o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Yet, AM hosts are prevalent throughout northern and central latitudes in Europe [19], and a global survey failed to find any correlation between SOM and abundance of AM fungi [20]. Further, AM fungi and their plant hosts can be widespread in SOM-rich ecosystems, including alpine meadows [21], tropical cloud forests [22], and the Arctic [23]. Although AM fungal community composition may shift with SOM at a global level [24] if not a landscape level [25], AM fungi and their hosts clearly are not restricted to mineral soils.…”
Section: A Hypothesis Of ‘Direct Mineral Cycling’mentioning
confidence: 99%
“…Yet, AM hosts are prevalent throughout northern and central latitudes in Europe [19], and a global survey failed to find any correlation between SOM and abundance of AM fungi [20]. Further, AM fungi and their plant hosts can be widespread in SOM-rich ecosystems, including alpine meadows [21], tropical cloud forests [22], and the Arctic [23]. Although AM fungal community composition may shift with SOM at a global level [24] if not a landscape level [25], AM fungi and their hosts clearly are not restricted to mineral soils.…”
Section: A Hypothesis Of ‘Direct Mineral Cycling’mentioning
confidence: 99%
“…As in other High Arctic ecosystems, symbiotic arbuscular mycorrhizal fungi are infrequent in the roots of grasses and forbs on the peninsula (Newsham et al 2017), but the vascular plant species Salix polaris, Cassiope tetragona, Bistorta vivipara and Dryas octopetala consistently form ectomycorrhizal or ericoid mycorrhizal symbioses with soil fungi (Geml et al 2012;Blaalid et al 2014;. These symbioses promote plant growth primarily by enhancing the acquisition of limiting nutrients (typically N and P) from the soil.…”
Section: Soil Microbial Communitiesmentioning
confidence: 98%
“…Overall, although studies suggest that the presence of AM fungal symbiosis is low in the Arctic at the level of both plant species (Allen et al ., 2006; Newsham et al ., 2017) and individuals (Newsham et al ., 2017), cases of high root colonization by AM fungal structures have still been reported (Olsson et al ., 2004; Ormsby et al ., 2007), as have several species of AM fungi (Greipsson et al ., 2002; Öpik et al ., 2013). It thus appears that there is still much to learn about AM fungal diversity in the Arctic and how it relates to plant species identity.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to AM fungal colonization of roots, several studies from the Arctic nonetheless have found colonization levels ranging from 11-36% root length colonized (Allen et al, 2006), through 27-51% root length colonized (Ormsby et al, 2007), to 37-85% root length colonized (Olsson et al, 2004). Newsham et al (2017) studied 102 plants from 11 plant species, and found structures resembling AM fungi in 41 of the plant individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation